CONTRIBUTION OF LIGNITE IN THE GREEK ECONOMY - Karageorgiou, D. E.; Metaxas, A.; Dimitriou, D.; Arapogiannis, E.; Varvarousis, G. (Bulletin of the Geological Society of Greece, 2010)
The objective of the present work is the assessment of the lignite contribution to the energy balance of Greece, according to the creation processes and the chronological classification. The lignite deposits known so far in Greece have been discovered and researched from the scientists of IGME in the course of evolution since 1948 (Greek Geological Survey), 1950 (Institute of Geology and Surface Research), 1973 (National Institute of Geological and Mineral Exploration) and finally in its current form in 1976 (Institute of Geology and Mineral Exploration) and are divided into (a) “productive”, (b) future “productive” and (c) no financial interest in power generation. A project, co-financed by the Greek Government and the European Union, is currently implemented, aiming at the recovery of the latter in non-electrical purposes with very good results in the first stage of research. According to the works carried out so far it has been observed that lignite formation started in Greece during Eocene and continued to date. From 1950 until today there is an upward trend in lignite reserves. Lignite generates electricity at a rate 63% today with higher rates 79.3%, during 1994. In Greece 41% of lignite deposits were created during Miocene. However, only 13% of these deposits that contribute to electricity generation derive from economically exploitable reserves. In Greece, due mainly to use of lignite for electricity production, the cost of Kw/h for both domestic use and for industrial is below the European Union average.